Pelatihan Optimasi Media Sosial Untuk Peningkatan Omzet UMKM - Kusuma, Rahma Djati; Sutjipto, Suci Sri Utami; Sujana, Sujana; Maretha, Hildha Aulia (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
This community service activity (PKM) aims to increase UMKM players' understanding of the importance of social media for business continuity, then provide guidance so that UMKM have an Instagram account for business and can use it effectively in accordance with best practices. This Social Media Optimization Training for Increasing UMKM Turnover is expected to provide understanding and the ability of UMKM players in using their business social media accounts so that they have an impact on business development and increase their turnover. The methods used in this training include (1) lectures to explain current Indonesian digital data, (2) discussion to find out the problems faced by UMKM related to social media, and (3) simulation as a practical session so that it is hoped that UMKM actors will better understand and master how. use of Instagram social media for business. This PKM activity has been carried out and is running smoothly in accordance with the objectives to be achieved, and getting good results. In general, the training participants, namely 100 UMKM champions in Bogor City, gave a positive response to the overall implementation of the training. This is because the material they get from this training is in accordance with their needs and is packaged in a fun event. Full support and appreciation from the Head of the Bogor City Cooperative and UMKM Office was given to the implementation team and the LPPM of the Unitary Business and Informatics Institute starting from the assessment or observation stage, to the implementation of training. The collaboration that has been established between the Unitary Business and Informatics Institute with UMKM actors as well as the Bogor City Cooperative and UMKM Office is expected to continue and be developed in the future as a form of implementing the Tridharma of Higher Education. Keywords: social media, UMKM